2016
DOI: 10.1111/dar.12389
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial of a computer-delivered screening and brief intervention for postpartum alcohol use

Abstract: Introduction and Aims Most women cut down or quit alcohol use during pregnancy, but return to pre-pregnancy levels of use after giving birth. Universal screening and brief intervention (SBI) for alcohol use has shown promise, but has proven challenging to implement and has rarely been evaluated with postpartum women. This trial evaluated a single 20-minute, electronic SBI (e-SBI) for alcohol use among postpartum women. Design and Methods In this parallel group randomised trial, 123 postpartum, low-income, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 54 publications
1
47
0
6
Order By: Relevance
“…Several studies reported on the acceptability of their interventions to participants and generally reported positive to very positive ratings. 79,97,116,117,130 Findings in the current review were generally consistent with the findings of the previous USPSTF review. 176 For test accuracy, the previous reviewers concluded that a single-question screener, the AUDIT-C, and the AUDIT appeared to be the best overall instruments for screening adults for the full spectrum of unhealthy alcohol use in primary care, with ranges of sensitivities and specificities solidly in the range of the sensitivities and specificities seen in this review among studies of adults.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies reported on the acceptability of their interventions to participants and generally reported positive to very positive ratings. 79,97,116,117,130 Findings in the current review were generally consistent with the findings of the previous USPSTF review. 176 For test accuracy, the previous reviewers concluded that a single-question screener, the AUDIT-C, and the AUDIT appeared to be the best overall instruments for screening adults for the full spectrum of unhealthy alcohol use in primary care, with ranges of sensitivities and specificities solidly in the range of the sensitivities and specificities seen in this review among studies of adults.…”
Section: Discussionsupporting
confidence: 87%
“…Few studies have been conducted applying digital BIs to reduce drinking during pregnancy [28,29]; however, postpartum drinking has received limited attention so far. Ondersma et al [30] evaluated the effect of a computer-based BI on 7-day point-prevalence abstinence and drinking days among postpartum women. Postpartum women with an elevated risk for alcohol use (n = 123; ≥ 4 standard drinks at a time at least twice per month in the 12 months pre-pregnancy, and ≥ 2 on the T-ACE [31]) were recruited and randomized to computer-based BI or AO.…”
Section: Brief Interventionsmentioning
confidence: 99%
“…Technology‐based interventions (TBIs) are increasingly being studied and utilized to facilitate translation of clinical interventions into a platform that is convenient, cost‐effective, and easily disseminated (Litvin et al., ). Relative to face‐to‐face interventions, TBIs afford numerous advantages such as greater ease and reliability of implementation, anonymity, accessibility, and personalization (Ondersma et al., ). These interventions, compared to face‐to‐face ones, can be accessed at times and locations that suit the needs of the patient and/or treatment setting, thus expanding the potential to reach a greater number of patients and ultimately to have a larger impact (Glasgow et al., ).…”
mentioning
confidence: 99%